Factors that Differentiate Preadolescents' Perception-Change of Parental Legitimacy - Edwards, Laura; Rodrigues, Herbert; Thomas, Kendra (International Journal of Child, Youth and Family Studies, 2020)
Whether preadolescents perceive their parents’ authority as legitimate or not depends, in part, on the concerns and issues that they have dealt with before and during their preadolescence. Utilizing data from the first and second waves of the São Paulo Legal Socialization Study (SPLSS), we conducted one-way MANOVAs to analyze the role of procedural justice and the impact of victimization on preadolescents’ perceptions of parental legitimacy across domains. Preadolescents were split into four distinct groups based on their perceptions of parental legitimacy and whether the perception shifted across the two waves of data. The study revealed a significant difference across groups in terms of procedural justice and on preadolescents’ reported victimization levels. The latter indicate that suffering some form of victimization may have resulted in delegitimizing parental authority. The findings broaden the literature on parenting practices in preadolescence and make salient an emerging field of victimization impacting parental legitimacy.